Tunable photoluminescence in a van der Waals heterojunction built from a MoS2 monolayer and a PTCDA organic semiconductor. Issue 34 (16th August 2018) - Habib, Mohammad Rezwan; Li, Hongfei; Kong, Yuhan; Liang, Tao; Obaidulla, Sk. Md.; Xie, Shuang; Wang, Shengping; Ma, Xiangyang; Su, Huanxing; Xu, Mingsheng
Abstract : We observe synergistic photoluminescence of MoS2 /PTCDA vdW heterostructure due to the interface interaction and improved crystal of PTCDA layer. Abstract : We report the photoluminescence (PL) characteristics of a van der Waals (vdW) heterojunction constructed by simply depositing an organic semiconductor of 3, 4, 9, 10-perylene tetracarboxylic dianhydride (PTCDA) onto a two-dimensional MoS2 monolayer. The crystallinity of PTCDA on MoS2 is significantly improved due to the vdW epitaxial growth. We observe an enhanced PL intensity and PL peak shift of the MoS2 /PTCDA heterojunction compared with the solo MoS2 and PTCDA layer. The synergistic PL characteristics are believed to originate from the hybridization interaction between the MoS2 and the PTCDA as evidenced by density functional theory calculations and Raman measurements. The hybridization interfacial interaction is found to be greatly influenced by the crystalline ordering of the PTCDA film on the 2D MoS2 . Our study opens up a new avenue to tune the PL of vdW heterojunctions consisting of TMDs and organic semiconductors for optoelectronic applications.